2023
DOI: 10.1590/1983-1447.2023.20220093.en
|View full text |Cite
|
Sign up to set email alerts
|

Educational technologies for HIV prevention in black people: scope review

Abstract: Objective: To map the educational technologies implemented for HIV prevention in black people. Method: Scope review, performed according to the recommendations of The Joanna Briggs Institute, in Medline/PubMed, Embase, LILACS, CINAHL, Scopus, Cochrane and PsycINFO databases, using the Preferred Reporting Items for Systematic reviews and Meta- Analyses extension for Scoping Reviews (PRISMA-ScR). Results: There were 14 studies published between 1999 and 2020. The main health impacts for black people involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It is not surprising that tenants might be less willing to modify home hazards, which are likely to increase the risk of falling. Several environmental risk factors have been identified, such as a cluttered environment, dim room, no antislip material in bath/shower, without grab bars on the doorway and toilets [24]. Second, people without their own houses also suggested that they may need to move frequently and live in unfamiliar environments.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that tenants might be less willing to modify home hazards, which are likely to increase the risk of falling. Several environmental risk factors have been identified, such as a cluttered environment, dim room, no antislip material in bath/shower, without grab bars on the doorway and toilets [24]. Second, people without their own houses also suggested that they may need to move frequently and live in unfamiliar environments.…”
Section: Discussionmentioning
confidence: 99%

Nursing Care for Patients With Human Immunodeficiency - Hiv

Pereira Nunes,
Lívia Silva Fonseca Moreira de Medeiro,
Gonçalves Leoncio Batista
et al. 2024
hs